Online Learning for Higher Education Continuity (during COVID-19 Pandemic) the Challenges, Advantages, Disadvantages, and How to Overcome: Recent Advancement - Abdulkareem, Talal A.; Eidan, Sajeda M. (Modern Perspectives in Economics, Business and Management Vol. 1, 2021)
The COVID-19 pandemic has undoubtedly disrupted the higher education sector worldwide leading to the near-total closures of universities and colleges. This situation creates a series of challenges that can deepen inequalities across societies which now forced to move into the online realm. Almost all universities shifted face-to-face education to remote or online learning. Significant obstacles have been created for the global higher education community. This chapter focused on the challenges that faced the higher education sector in many countries worldwide during a COVID-19 pandemic and how the remote learning and related techniques, platforms, and other online implications were supporting the continuity of this utmost important sector during the new normal era. Challenges, advantages, and disadvantages of applying these technologies by instructors and students and how to overcome these negatives will also discuss herein.